Electrochemical Dearomatization: Evolution from Chemicals to Traceless Electrons - Lv, Shide; Zhang, Guofeng; Chen, Jianbin; Gao, Wei (Advanced synthesis & catalysis, 2020)
Dearomatization reactions represent a versatile approach for the preparation of three‐dimensionally (3D) privileged cyclic moieties from simple planar aromatic compounds. However, exogeneous oxidants are required for most of the radical and oxidative dearomatizations. Therefore, sustainable procedures are in high demand, especially those in the absence of external oxidizing reagents. Fortunately, electrolytic dearomatization protocols can fulfill the above requirements due to the manipulation of traceless electrons instead of chemicals during the processes. Nevertheless, sustainable electrochemical dearomative transformations have been far less frequently investigated than the well‐developed chemical dearomatization reactions. Herein, we summarize representative breakthroughs in the electrochemical dearomative transformation of indoles, furans and activated arenes (phenols and anisoles) for the synthesis of complicated skeletons. Hopefully, this interesting “simplicity‐to‐complexity” synthetic logic will inspire more innovations from the electroorganic community.